Assessment of the wheat growth-promoting potential of Delftia lacustris strain NSC through genomic and physiological characterization - Sharma, Pinki; Pandey, Rajesh; Chauhan, Nar Singh (Frontiers in Microbiology, 2025)
BackgroundDelftia species have attracted significant interest for their biofertilizer and biocontrol capabilities, particularly in promoting the growth of crops such as Oryza sativa, Brassica campestris, and Solanum lycopersicum. However, their potential in supporting wheat cultivation remains largely unexplored.MethodsA culture-dependent approach was employed to isolate a Delftia strain from the wheat rhizosphere. The biofertilizer potential of the isolate was systematically evaluated through a series of physiological, biochemical, and molecular assays, as well as field trials to assess its efficacy under agronomic conditions.Results and discussionCulture-dependent investigation of the wheat rhizosphere led to the isolation of a multifunctional plant growth-promoting bacterium, designated as strain NSC. Morphological and physiological characterization identified NSC as a gram-negative, rod-shaped, motile bacterium with optimal growth at pH 7.0 and 35°C. Phylogenetic and phylogenomic analyses confirmed its taxonomic identity as Delftia lacustris. In vitro assays revealed its ability to solubilize phosphate (0.325 IU), reduce nitrate (0.401 IU), produce indole-3-acetic acid (0.485 IU), and exhibit ACC deaminase activity (0.512 IU) and siderophore production. The strain demonstrated strong antifungal activity against Fusarium oxysporum and Rhizoctonia solani. Strain NSC exhibited significant tolerance to abiotic stresses, including drought [up to 40% PEG (w/v)], heavy metals, and high salinity [up to 11.69% NaCl (w/v), 11.18% KCl (w/v), and 4.24% LiCl (w/v)]. Genome analysis identified key genes associated with phosphate solubilization (PhoR, PhoB, PhoU, PstABCD), nitrogen fixation (nifC, nifU), auxin and siderophore biosynthesis, rhizosphere colonization, and antifungal mechanisms (chitinase, PhnZ). In planta studies showed significantly enhanced seed germination (93.33% ± 0.23), seedling growth, and biomass accumulation under stress conditions (p < 0.05). Field trials further validated the strain’s efficacy, showing marked improvements in plant growth and yield parameters (p = 0.0001). These results underscore the potential of D. lacustris NSC as an effective biofertilizer and biocontrol agent for sustainable agriculture.ConclusionDelftia lacustris strain NSC exhibits multifunctional plant growth-promoting and biocontrol activities, including enhanced nutrient mobilization, pathogen suppression, and abiotic stress tolerance. Its demonstrated efficacy under field conditions and environmentally benign profile highlight its potential as a sustainable bioinoculant for wheat production systems.